1998
DOI: 10.1161/01.cir.98.6.541
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Sustained Ventricular Tachycardia in Myotonic Dystrophy

Abstract: A high clinical suspicion of bundle-branch reentrant tachycardia is justified in patients with myotonic dystrophy who exhibit wide QRS complex tachycardia or tachycardia-related symptoms. Because catheter ablation will easily and effectively abolish bundle-branch reentrant tachycardia, myotonic dystrophy should always be considered in patients with sustained ventricular tachycardia. This is especially true if no apparent heart disease is found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(78 citation statements)
references
References 33 publications
2
70
1
5
Order By: Relevance
“…These results suggest that fatty-fibrosis may become a point of origin of ventricular arrhythmia. Several authors have reported that the mechanism of VT in DM1 might be due to His-Purkinje conduction delay caused by massive fatty fibrosis (11,13). Additionally, it was recently reported that the focal fatty degeneration of the right ventricle could be demonstrated by MRI in patients with DM1 (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that fatty-fibrosis may become a point of origin of ventricular arrhythmia. Several authors have reported that the mechanism of VT in DM1 might be due to His-Purkinje conduction delay caused by massive fatty fibrosis (11,13). Additionally, it was recently reported that the focal fatty degeneration of the right ventricle could be demonstrated by MRI in patients with DM1 (17).…”
Section: Discussionmentioning
confidence: 99%
“…Most cardiac events consist of impairment of the cardiac conduction system including bundle branch block or atrioventricular block. These are few reports of ventricular tachycardia (VT), whereas ventricular arrhythmias play a major role in the mortality of these patients (9)(10)(11)(12)(13). Unfortunately, pharmacological therapies have not significantly improved the prognosis (14), possibly due to the massive fatty fibrosis in the cardiac muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some VTs failing to show these responses in the present and other 3,4 studies could have been included in the MR-VT group despite having a BBR mechanism. BBR is highly unlikely in the absence of significant His-Purkinje disease, [3][4][5] however, and except for 10 MR-VT patients, none showed prolonged QRS complex (Ͼ120 ms) or HV interval (Ͼ60 ms) during sinus rhythm in the present study. In 9 of these 10 patients, BBR was considered highly unlikely because the His bundle electrogram showed no 1:1 tachycardia association, because there were supraventricular captures with a different QRS-complex morphology, or because the His bundle electrogram followed the onset of the QRS complex and preceded the perihisian ventricular activation.…”
Section: Study Limitationsmentioning
confidence: 55%
“…3,4 BBR-VT diagnosis was established according to previously published criteria (criteria A) [2][3][4]6 : (1) QRS-complex morphology with typical BBB pattern consistent with ventricular depolarization through the appropriate bundle branch; (2) AV dissociation during tachycardia; (3) exclusion of a tachycardia from supraventricular origin by established criteria; (4) prolonged HV interval during sinus rhythm; (5) a stable His or bundle-branch electrogram preceding each ventricular activation during tachycardia with an HV interval longer than, equal to, or Ͻ10 ms shorter than that recorded during sinus rhythm; and (6) spontaneous changes in the bundle potential CL preceding similar changes in the ventricular CL. Because BBR has been found to be the tachycardia mechanism despite criterion 6 not being demonstrated, 5,8 BBR-VT diagnosis was also established when all the following criteria (criteria B) were fulfilled: (1) all 6 criteria A were fulfilled except for criterion 6, that is, spontaneous changes in the bundle potential CL followed rather than preceded similar changes in the ventricular CL; (2) Ն1 additional BBR-VT morphologies were also inducible and fulfilled all criteria A; (3) the difference in tachycardia CL was Յ30 ms compared with those of the other induced BBR-VTs; (4) no MR-VT, either sustained or nonsustained, was inducible; (5) the patient had no structural heart disease; and (6) the inducibility of all tachycardias was suppressed after bundle-branch ablation. Finally, observation of orthodromic concealed fusion (concealed fusion with tachycardia QRS-complex morphology preservation) during entrainment by pacing from the atrium was an additional criterion sufficient but not mandatory to distinguish BBR-VT from MR-VT. 6 Suppression of inducibility after right or, in patient 6, left bundle-branch ablation, both at baseline and during isoproterenol infusion, was achieved in all except 2 entrained BBR-VTs.…”
Section: Tachycardia Mechanism Definitionsmentioning
confidence: 99%
See 1 more Smart Citation